Thermal and physicochemical properties of starches from three Colombian rice varieties (2017)
Samples of starch from broken grains of three rice varieties grown in Colombia were analyzed to determine their physicochemical and thermal properties: Fedearroz 473 (F473), Fedearroz 50 (F50) and Fedearroz 60 (F60). The granule size, solubility, swelling capacity, amylose content, syneresis, turbidity, thermal and pasting properties of starches were determined. The average size of starch granules was 9.4, 7.4 and 7.2 μm for F473, F50 and F60 samples, respectively. The amylose content showed significant differences between the studied varieties and ranged between 21.4% and 23.0%. Turbidity ranged between 1.95 and 2.34 absorbance units at 620 nm. Thermal properties, evaluated by differential scanning calorimetry (DSC), registered values between 61.6 and 64.6°C for the onset temperature, between 66.6 and 69.3°C for the peak temperature, between 72.1 and 73.9°C for the end temperature, and between 8.38 and 9.47 J g-1 for the gelatinization enthalpy. The higher amylose content the higher grain size, turbidity, syneresis, viscosity, gelatinization temperature and enthalpy, and the lower swelling capacity and solubility. This paper is the first reported research on physicochemical and functional properties of starches from these Colombian rice varieties.